Carbon-based adsorption material for treating heavy metal contaminated soil

By using the combination of auxiliary materials such as surface functional activated carbon and bentonite in carbon-based adsorption materials, combined with the chemical solid-load technology of surface functional macromolecular reagents, the problem of insufficient stability and adsorption capacity of existing carbon-based adsorption materials is solved, and a more efficient and stable effect of heavy metal contaminated soil treatment is achieved.

CN119565567AActive Publication Date: 2025-03-07GUANGDONG AGRI ENVIRONMENT INSPECTION & TESTING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411845696.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-07
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

When using heavy metal contaminated soil, existing carbon-based adsorption materials have low physical adsorption stability, which is prone to secondary pollution, and have limited adsorption capacity, which limits their application effect.

Method used

Surface functionalized activated carbon is used as the main substance, and through the combination with auxiliary materials such as bentonite and fly ash, the ultra-high specific surface area of ​​activated carbon and bentonite is used for adsorption, and chemical solid support is carried out through the active groups in the structure of surface functionalized macromolecular reagents to form an adsorption first-and then solid support.

Benefits of technology

It improves the adsorption capacity and stability of adsorbent materials, avoids the occurrence of secondary pollution, and expands the adsorption capacity, significantly improving the effect of treating heavy metal-contaminated soil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565567A_ABST
    Figure CN119565567A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of materials, and discloses a carbon-based adsorption material for treating heavy metal contaminated soil, the carbon-based adsorption material is prepared by using surface functionalized activated carbon as a base material and bentonite and fly ash as auxiliary materials, bonding by using biomass guar gum, and then mixing and sintering. According to the method, surface functionalized activated carbon is used as a main substance of an adsorption material, bentonite, fly ash and the like are used as auxiliary materials, and heavy metal ions in soil are adsorbed and enriched through the ultrahigh specific surface area of the activated carbon and the bentonite; the heavy metal ions are subjected to chemical immobilization by using active groups in the surface functionalized macromolecular reagent structure, and an adsorption mode of adsorption first and then immobilization is formed, so that the prepared adsorption material has extremely high adsorption capacity, and the phenomenon of secondary pollution is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material technology, and in particular to a carbon-based adsorption material for treating heavy metal-contaminated soil. Background Art

[0002] With the acceleration of industrialization, heavy metal pollution has become one of the severe challenges facing the soil environment worldwide. Heavy metals such as lead, cadmium, chromium, and mercury pose a huge threat to the ecosystem and human health because they are difficult to degrade, easily accumulate in organisms, and are transmitted along the food chain. Therefore, it is particularly important to develop efficient and environmentally friendly heavy metal contaminated soil remediation technologies. Among the many heavy metal contaminated soil remediation methods, carbon-based adsorption materials have gradually become a research hotspot for the treatment of heavy metal contaminated soil due to their excellent adsorption performance, environmental friendliness, and renewability.

[0003] Carbon-based adsorption materials mainly include activated carbon, biochar, graphene and its derivatives, etc. They have the characteristics of large specific surface area, rich pore structure, and diverse surface functional groups. These characteristics enable them to effectively adsorb and fix heavy metal ions in the soil. The carbon-based adsorption materials are directly applied to the contaminated soil to capture heavy metal ions by physical adsorption, reducing their mobility and bioavailability in the soil. Since this method is easy to operate, it is widely used. However, most conventional carbon-based adsorption materials can only fix heavy metal ions in the pores by physical adsorption. This physical fixation method is not very stable, prone to secondary pollution, and has limited adsorption capacity. These defects actually have a great impact on the application of carbon-based adsorption materials in heavy metal contaminated soils. Therefore, it is of great significance to develop carbon-based adsorption materials with strong stability and good adsorption effect. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the deficiencies of the prior art, the present invention provides a carbon-based adsorption material for treating heavy metal contaminated soil.

[0006] (II) Technical solution

[0007] A carbon-based adsorption material for treating heavy metal-contaminated soil, comprising the following raw materials measured in parts by weight:

[0008]

[0009] As a further embodiment of the present invention, the method for preparing the carbon-based adsorption material comprises the following steps:

[0010] Step 1: mechanically stir and mix the surface functionalized activated carbon, bentonite, biomass adhesive, fly ash and paraffin wax in parts by weight to form a slurry;

[0011] Step 2: Transfer the slurry to a mold, let it stand for 10-30 minutes, and then extrude it to form a blank. Then place the blank in a sintering furnace, increase the temperature to 280-320°C at a heating rate of 3-5°C / min, take it out after 1-3 hours, let it cool naturally, crush it, and pass it through an 80-100 mesh sieve to obtain a carbon-based adsorption material.

[0012] As a further embodiment of the present invention, the specific preparation method of the surface functionalized activated carbon comprises the following steps:

[0013] Step S1, immersing the doped activated carbon in concentrated nitric acid, performing an acidification treatment at a temperature of 90-100° C. for 1-3 hours, taking it out, washing it to neutrality, and then drying it to form acidified activated carbon;

[0014] Step S2, adding the acidified activated carbon to tetrahydrofuran, ultrasonically treating for 20-30 minutes to form a uniform dispersion, then adding the composite catalyst to the dispersion, stirring at room temperature for 1-2 hours, and then adding the surface functionalized macromolecular reagent to the dispersion. After the addition is completed, stirring is continued at room temperature for 4-8 hours, discharging, separating the solid, washing, and vacuum drying to obtain the surface functionalized activated carbon.

[0015] In the above technical scheme, the doped activated carbon is firstly treated with acid by concentrated nitric acid to produce active carboxyl substituents on its surface, and then the carboxyl substituents are catalyzed by a composite catalyst to undergo esterification condensation with the hydroxyl groups in the structure of the surface functionalized macromolecular reagent, thereby modifying the surface of the activated carbon with the surface functionalized macromolecular reagent to obtain surface functionalized activated carbon.

[0016] As a further solution of the present invention, in step S1, the specific preparation method of the doped activated carbon comprises the following steps:

[0017] Step SS1, adding gellan gum to N,N-dimethylformamide, stirring and dispersing evenly, then adding isocyanate monomer and dibutyltin dilaurate, mixing evenly, raising the temperature to 70-80°C, stirring and keeping warm for 6-12 hours, stopping heating, cooling and discharging, and forming a cross-linked carbon precursor;

[0018] Step SS2: Grind and mix the cross-linked carbon precursor and potassium hydroxide evenly, then place them in a tubular furnace for carbonization treatment. After the carbonization treatment is completed, take them out, wait for them to cool naturally, wash them to neutrality, and dry them completely to obtain doped activated carbon.

[0019] As a further embodiment of the present invention, in step SS1, the isocyanate monomer is any one of toluene diisocyanate, isophorone diisocyanate or dicyclohexylmethane diisocyanate.

[0020] As a further solution of the present invention, in step SS2, the temperature during the carbonization treatment is 700-750°C, and the carbonization is carried out for 1-3 hours under nitrogen protection.

[0021] In the above technical scheme, isocyanate monomer is used as a cross-linking agent to cross-link gellan gum to form a cross-linked carbon precursor, cross-linked gellan gum is used as a carbon source, isocyanate monomer is used as a nitrogen source, potassium hydroxide is used to activate and form pores, and then high-temperature carbonization is performed to obtain nitrogen-doped activated carbon.

[0022] As a further solution of the present invention, in step S2, the composite catalyst is a mixture of dicyclohexylcarbodiimide and 4-dimethylaminopyridine, with a mass ratio of 1:0.3-0.4.

[0023] As a further solution of the present invention, in step S2, the specific preparation method of the surface functionalized macromolecular reagent comprises the following steps:

[0024] Step SSS1, adding 3,5-dihydroxybenzonitrile and ethylene glycol diglycidyl ether to toluene, stirring until completely dissolved to form a uniform reaction liquid, then adding boron trifluoride ether complex to the reaction liquid, introducing nitrogen protection, raising the temperature to 80-90° C., stirring continuously, keeping warm for 8-12 hours, discharging the material, and obtaining a macromolecular precursor;

[0025] Step SSS2, mixing a 1-2 mol / L hydroxylamine hydrochloride solution with a 0.4-0.6 mol / L sodium carbonate solution to form a uniform mixed solution, then adding the macromolecular precursor to the mixed solution, and then controlling the temperature to 70-80°C, stirring for 4-6 hours, cooling and discharging the material, washing and vacuum drying, and then obtaining a surface functionalized macromolecular reagent.

[0026] As a further embodiment of the present invention, in step SSS1, the molar ratio of 3,5-dihydroxybenzonitrile to ethylene glycol diglycidyl ether is 1:0.8-0.9.

[0027] As a further embodiment of the present invention, in step SSS2, the volume ratio of the hydroxylamine hydrochloride solution to the sodium carbonate solution is 1:1.

[0028] In the above technical scheme, 3,5-dihydroxybenzonitrile and ethylene glycol diglycidyl ether are first used as polymerization monomers. Under the catalytic action of boron trifluoride ether complex, the active hydroxyl groups and epoxy groups between each other can undergo continuous ring-opening reactions to form block-alternatingly connected macromolecules, i.e., macromolecular precursors. Then, hydroxylamine hydrochloride is used to convert the cyano group in its structure into amidoxime groups, and finally a surface functionalized macromolecular reagent containing a large number of amidoxime groups in its structure is obtained.

[0029] (III) Beneficial technical effects

[0030] The present invention prepares surface functionalized activated carbon by using a surface functionalized macromolecular reagent containing a large number of amidoxime groups in the surface modification structure of nitrogen-doped activated carbon. First, the surface functionalized macromolecular reagent structure contains a large number of hydroxyl groups that do not participate in the reaction, as well as a large number of ether bonds and amidoxime groups, wherein the active hydroxyl groups and amidoxime groups can produce chelation and coordination effects on heavy metal ions in the soil, and chemically adsorb the heavy metal ions. This chemical adsorption is relatively stable and can prevent the phenomenon of secondary pollution. In addition, the adsorption capacity of the adsorbent material can also be increased. Secondly, the activated carbon is doped with nitrogen, and the lone pair of electrons of the nitrogen element can also produce complexation effects on heavy metal ions, thereby further improving the adsorption effect of the activated carbon.

[0031] The present invention adopts surface functionalized activated carbon as the main substance of the adsorption material, and uses bentonite, fly ash and the like as auxiliary materials. The ultra-high specific surface area of ​​activated carbon and bentonite is used to achieve adsorption and enrichment of heavy metal ions in the soil. Then, the active groups in the structure of the surface functionalized macromolecular reagent are used to chemically immobilize the heavy metal ions, forming an adsorption mode of first adsorption and then immobilization. The prepared adsorption material can have extremely strong adsorption capacity and will not cause secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0033] Figure 1 This is a scanning electron microscope image of doped activated carbon;

[0034] Figure 2 This is the infrared test image of the surface functionalized macromolecular reagent. DETAILED DESCRIPTION

[0035] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0036] Preparation Example 1

[0037] Preparation of surface functionalized activated carbon:

[0038] Step S1, immersing the doped activated carbon in concentrated nitric acid, performing an acidification treatment at a temperature of 95° C. for 2 hours, taking it out, washing it to neutrality, and then drying it to form acidified activated carbon;

[0039] Step S2, adding 1.5 g of acidified activated carbon to tetrahydrofuran, ultrasonically treating for 30 min to form a uniform dispersion, then adding 0.5 g of dicyclohexylcarbodiimide and 0.2 g of 4-dimethylaminopyridine to the dispersion, stirring at room temperature for 1 h, and then adding 4 g of surface functionalized macromolecular reagent to the dispersion. After the addition is completed, stirring is continued at room temperature for 6 h, discharging, separating the solid, washing, and vacuum drying to obtain surface functionalized activated carbon.

[0040] The preparation method of doped activated carbon is as follows:

[0041] Step SS1, add 3g of gellan gum to N,N-dimethylformamide, stir and disperse evenly, then add 0.6g of toluene-2,4-diisocyanate and 0.01g of dibutyltin dilaurate, mix well, raise the temperature to 75°C, stir and keep warm for 9h, stop heating, cool and discharge, and form a cross-linked carbon precursor;

[0042] Step SS2: Grind and mix 1.8 g of cross-linked carbon precursor and 7 g of potassium hydroxide evenly, then place them in a tubular furnace under nitrogen protection and carbonize them at a carbonization temperature of 750°C for 2 hours. After the carbonization, take them out, wait for them to cool naturally, wash them to neutrality, and dry them completely to obtain doped activated carbon.

[0043] Figure 1 This is a scanning electron microscope image of doped activated carbon. It can be clearly observed that it has a rich pore structure and presents an overall "honeycomb" type porous structure.

[0044] The specific preparation method of the surface functionalized macromolecular reagent comprises the following steps:

[0045] Step SSS1, add 0.3 g of 3,5-dihydroxybenzonitrile and 0.32 g of ethylene glycol diglycidyl ether to toluene, stir until completely dissolved to form a uniform reaction solution, then add 0.01 g of boron trifluoride ether complex to the reaction solution, pass nitrogen protection, raise the temperature to 85°C, stir continuously, keep warm for 9 hours, and then discharge the material to obtain a macromolecular precursor;

[0046] Step SSS2: Mix 20 mL of 1 mol / L hydroxylamine hydrochloride solution with 20 mL of 0.5 mol / L sodium carbonate solution to form a uniform mixed solution, then add 1 g of the macromolecular precursor to the mixed solution, and then control the temperature to 70°C. After stirring for 6 hours, cool the material, wash it, and vacuum dry it to obtain a surface functionalized macromolecular reagent.

[0047] Figure 2 This is the infrared test image of the surface functionalized macromolecular reagent. The analysis shows that 3439cm -1 The characteristic absorption peak at 3301 cm is the NH absorption peak of the amidoxime group. -1 The characteristic absorption peak at 3000-3100cm -1 The characteristic absorption peak at 1654 cm is the characteristic absorption peak of the benzene ring skeleton. -1 The characteristic absorption peak at 1096 cm is the C=N characteristic absorption peak of the amidoxime group. -1 The characteristic absorption peak appearing at is the characteristic absorption peak of the ether bond produced by the ring-opening reaction.

[0048] Example 1

[0049] A carbon-based adsorption material for treating heavy metal-contaminated soil, comprising the following raw materials measured in parts by weight:

[0050]

[0051] The method for preparing the carbon-based adsorption material comprises the following steps:

[0052] Step 1: mechanically stir and mix the surface functionalized activated carbon, bentonite, biomass adhesive, fly ash and paraffin wax in parts by weight to form a slurry;

[0053] Step 2: Transfer the slurry to a mold, let it stand for 10 minutes, and then extrude it to form a blank. Then place the blank in a sintering furnace, increase the temperature to 280°C at a heating rate of 5°C / min, take it out after 3 hours, let it cool naturally, crush it, and pass it through an 80-mesh sieve to obtain a carbon-based adsorption material.

[0054] The preparation method of the surface functionalized activated carbon is shown in Preparation Example 1, and the same is true for the following.

[0055] Example 2

[0056] A carbon-based adsorption material for treating heavy metal-contaminated soil, comprising the following raw materials measured in parts by weight:

[0057]

[0058] The method for preparing the carbon-based adsorption material comprises the following steps:

[0059] Step 1: mechanically stir and mix the surface functionalized activated carbon, bentonite, biomass adhesive, fly ash and paraffin wax in parts by weight to form a slurry;

[0060] Step 2: Transfer the slurry to a mold, let it stand for 20 minutes, and then extrude it to form a blank. Then place the blank in a sintering furnace, increase the temperature to 300°C at a heating rate of 5°C / min, take it out after 2 hours, let it cool naturally, crush it, and pass it through a 100-mesh sieve to obtain a carbon-based adsorption material.

[0061] Example 3

[0062] A carbon-based adsorption material for treating heavy metal-contaminated soil, comprising the following raw materials measured in parts by weight:

[0063]

[0064] The method for preparing the carbon-based adsorption material comprises the following steps:

[0065] Step 1: mechanically stir and mix the surface functionalized activated carbon, bentonite, biomass adhesive, fly ash and paraffin wax in parts by weight to form a slurry;

[0066] Step 2: Transfer the slurry to a mold, let it stand for 30 minutes, and then extrude it to form a blank. Then place the blank in a sintering furnace, increase the temperature to 320°C at a heating rate of 5°C / min, take it out after 1 hour, let it cool naturally, crush it, and pass it through a 100-mesh sieve to obtain a carbon-based adsorption material.

[0067] Comparative Example 1

[0068] A carbon-based adsorption material for treating heavy metal-contaminated soil, comprising the following raw materials measured in parts by weight:

[0069]

[0070] The method for preparing the carbon-based adsorption material comprises the following steps:

[0071] Step 1: Mix the doped activated carbon, bentonite, biomass adhesive, fly ash and paraffin by mechanical stirring according to weight to form a slurry;

[0072] Step 2: Transfer the slurry to a mold, let it stand for 20 minutes, and then extrude it to form a blank. Then place the blank in a sintering furnace, increase the temperature to 300°C at a heating rate of 5°C / min, take it out after 2 hours, let it cool naturally, crush it, and pass it through a 100-mesh sieve to obtain a carbon-based adsorption material.

[0073] The preparation method of doped activated carbon is shown in Preparation Example 1.

[0074] Comparative Example 2

[0075] A carbon-based adsorption material for treating heavy metal-contaminated soil, comprising the following raw materials measured in parts by weight:

[0076]

[0077] The method for preparing the carbon-based adsorption material comprises the following steps:

[0078] Step 1: Mix commercially available activated carbon, bentonite, biomass adhesive, fly ash and paraffin by mechanical stirring according to weight to form a slurry;

[0079] Step 2: Transfer the slurry to a mold, let it stand for 20 minutes, and then extrude it to form a blank. Then place the blank in a sintering furnace, increase the temperature to 300°C at a heating rate of 5°C / min, take it out after 2 hours, let it cool naturally, crush it, and pass it through a 100-mesh sieve to obtain a carbon-based adsorption material.

[0080] The commercially available activated carbon was purchased from the first-grade bamboo charcoal of Anhui Xingheng Environmental Protection Technology Co., Ltd., with a fixed carbon content of ≥90.0%.

[0081] Test Case

[0082] Extract heavy metal contaminated soil, completely remove the impurities therein, crush it through a 100 mesh sieve, add water and stir to prepare a test sample of 2L with a soil solid content of 200g / L, then add 10mL of hydrochloric acid solution with a concentration of 1mol / L to the test sample, stir at room temperature for 2h, let it stand for 30min, measure the heavy metal ion content in the supernatant, record it as m, then divide the test sample into 5 parts, add 1.5g of the carbon-based adsorption material in Examples 1-3 and Comparative Examples 1-2 to each part, after adding, continue stirring for 8h, let it stand for 30min, test the heavy metal ion content in the supernatant, record it as M, and calculate the adsorption rate by the formula [(mM) / m]×100%. The test results are shown in the following table:

[0083]

[0084] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

[0085] Based on the ideal embodiment of the present invention, through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A carbon-based adsorption material for treating heavy metal contaminated soil, characterized in that: It includes the following raw materials measured by weight:

2. The carbon-based adsorption material for treating heavy metal contaminated soil according to claim 1, characterized in that: The method for preparing the carbon-based adsorption material comprises the following steps: Step 1: mechanically stir and mix the surface functionalized activated carbon, bentonite, biomass adhesive, fly ash and paraffin wax in parts by weight to form a slurry; Step 2: Transfer the slurry to a mold, let it stand for 10-30 minutes, and then extrude it to form a blank. Then place the blank in a sintering furnace, increase the temperature to 280-320°C at a heating rate of 3-5°C / min, take it out after 1-3 hours, let it cool naturally, crush it, and pass it through an 80-100 mesh sieve to obtain a carbon-based adsorption material.

3. The carbon-based adsorption material for treating heavy metal contaminated soil according to claim 1, characterized in that: The specific preparation method of the surface functionalized activated carbon comprises the following steps: Step S1, immersing the doped activated carbon in concentrated nitric acid, performing an acidification treatment at a temperature of 90-100° C. for 1-3 hours, taking it out, washing it to neutrality, and then drying it to form acidified activated carbon; Step S2, adding the acidified activated carbon to tetrahydrofuran, ultrasonically treating for 20-30 minutes to form a uniform dispersion, then adding the composite catalyst to the dispersion, stirring at room temperature for 1-2 hours, and then adding the surface functionalized macromolecular reagent to the dispersion. After the addition is completed, stirring is continued at room temperature for 4-8 hours, discharging, separating the solid, washing, and vacuum drying to obtain the surface functionalized activated carbon.

4. The carbon-based adsorption material for treating heavy metal contaminated soil according to claim 2, characterized in that: In step S1, the specific preparation method of the doped activated carbon comprises the following steps: Step SS1, adding gellan gum to N,N-dimethylformamide, stirring and dispersing evenly, then adding isocyanate monomer and dibutyltin dilaurate, mixing evenly, raising the temperature to 70-80°C, stirring and keeping warm for 6-12 hours, stopping heating, cooling and discharging, and forming a cross-linked carbon precursor; Step SS2: Grind and mix the cross-linked carbon precursor and potassium hydroxide evenly, then place them in a tubular furnace for carbonization treatment. After the carbonization treatment is completed, take them out, wait for them to cool naturally, wash them to neutrality, and dry them completely to obtain doped activated carbon.

5. The carbon-based adsorption material for treating heavy metal contaminated soil according to claim 4, characterized in that: In step SS1, the isocyanate monomer is any one of toluene diisocyanate, isophorone diisocyanate or dicyclohexylmethane diisocyanate.

6. The carbon-based adsorption material for treating heavy metal contaminated soil according to claim 4, characterized in that: In step SS2, the temperature during the carbonization treatment is 700-750° C., and the carbonization is carried out for 1-3 hours under nitrogen protection.

7. The carbon-based adsorption material for treating heavy metal contaminated soil according to claim 3, characterized in that: In step S2, the composite catalyst is a mixture of dicyclohexylcarbodiimide and 4-dimethylaminopyridine in a mass ratio of 1:0.3-0.

4.

8. The carbon-based adsorption material for treating heavy metal contaminated soil according to claim 3, characterized in that: In step S2, the specific preparation method of the surface functionalized macromolecular reagent comprises the following steps: Step SSS1, adding 3,5-dihydroxybenzonitrile and ethylene glycol diglycidyl ether to toluene, stirring until completely dissolved to form a uniform reaction liquid, then adding boron trifluoride ether complex to the reaction liquid, introducing nitrogen protection, raising the temperature to 80-90° C., stirring continuously, keeping warm for 8-12 hours, discharging the material, and obtaining a macromolecular precursor; Step SSS2, mixing a 1-2 mol / L hydroxylamine hydrochloride solution with a 0.4-0.6 mol / L sodium carbonate solution to form a uniform mixed solution, then adding the macromolecular precursor to the mixed solution, and then controlling the temperature to 70-80°C, stirring for 4-6 hours, cooling and discharging the material, washing and vacuum drying, and then obtaining a surface functionalized macromolecular reagent.

9. The carbon-based adsorption material for treating heavy metal contaminated soil according to claim 8, characterized in that: In step SSS1, the molar ratio of 3,5-dihydroxybenzonitrile to ethylene glycol diglycidyl ether is 1:0.8-0.

9.

10. The carbon-based adsorption material for treating heavy metal contaminated soil according to claim 8, characterized in that: In step SSS2, the volume ratio of the hydroxylamine hydrochloride solution to the sodium carbonate solution is 1:1.

Citation Information

Patent Citations

  • Di-amidoxime group containing modified silica gel adsorbent and preparation method thereof

    CN103223333A

  • Soil heavy metal pollution barrier layer material as well as preparation method and application thereof

    CN113621381A

  • Method for improving soil heavy metal pollution by polymer adsorption method

    CN117225886A

  • Carbon-based adsorbent with high-efficiency adsorption performance on uranium as well as preparation method and application of carbon-based adsorbent

    CN117696009A

  • Iron-based biochar material, preparation therefor and use thereof in soil pollution control

    US20170282229A1